Building Information Modelling; Definition, Implementation and Evaluation in Supporting Development of Morotai Tourism Area - Dimas Nugraha; Nino Heri Setyoadi (LP2M Universitas Bina Mandiri Gorontalo, 2020)
The rapid development of science and technology in the 21st century affects all scientific disciplines, economics, and government, include digital technology for architect, design and construction. Indonesia Government Regulation Number 50 of 2011 declare Morotai Island as a National Tourism Strategic Zone. In 2018, the Research and Development Office for the Application of Settlement Technology planned to have Tourism Toilet in the Daruba Region, for visitors and local residents. This Toilet facilities is equipped with Biofilter Technology, Fast Sand Filter Technology, Reserve Osmose, and Sanita Pool. This application was also supported by the application of Building Information Modeling (BIM) technology which has been widely used in the construction sector with the aim of monitoring the realization between plans and development so that it is more precise and efficient. Based on this, the study wanted to see what is BIM, the extent to which the implementation and evaluation of its application in supporting the development of Tourism Areas in Morotai. This solution was obtained by collecting primary and secondary data. The method to get primary data was by conducting interview with Project Owner, Planning Consultant, Contractor. This evaluation model consists of four components to evaluate which are Design, Installation, Process and Product (Results). Result of the study. Building Information Modeling (BIM), as an increasing technology in the Architecture, Engineering and Construction (AEC) industry, has been applied to various research topics ranging from project planning, structural design, facility management, and others. Since the '90s, BIM has been implementing applications in several constructions in Indonesia, but it has not made significant progress. In Morotai's work, work was made based on field conditions. The work of BIM was carried out covering architectural, structural, and mechanical electrical and Plumbing (MEP) aspects. For architectural and MEP aspects use Archicad Software, while for structural use Tekla Design. The general description of the results of the architectural display of BIM is as follows. The Level of Design used in this BIM is Level of Design 5, or up to the Volume calculation level. Evaluation in BIM implementation make with Discrepancy Evaluation Model (DEM). Discrepancy Evaluation consist of 4 stages, Design, Instalation, Process, and Implementation. Conclusion of this study, The application of BIM in the initial replication construction project in Morotai has not been fully effective in accelerating the planning process to the construction of tourist toilets and the technology contained within it